Studying mechanical, acoustical and dielectric properties of SiO₂-filled polyester resin nanocomposites - Gorelov, B.M.; Polovina, O.I.; Gorb, A.M.; Czapla, Z.; Dacko, S. (Functional Materials, 2012)
Concentration effects of fumed silica on mechanical (static Young modulus, compression strength limit), acoustic (Lame constant, shear modulus, Young modulus, compression modulus, and Poisson’s ratio), and dielectric parameters of an unsaturated styrene-containing polyester resin have been experimentally studied. The degree of filling Cf,m was ranged from 0.5 to 5.0 w. %. Cf,m-dependences of all the parameters are proved to be non-regular, with their maximal deviations from initial values being at Cf,m < 1.5 %.